Bai' Al-Wafa And Hybrid Contract In Bmt Sidogiri East Java - Zenal Mutaqin, Dadang; Ahmad Suryadi, Rudi (Journal of Islamic Economic Studies, 2025)
Some Islamic financial institutions have implemented bai' al-wafa' although there is no DSN MUI fatwa that regulates directly. This academic debate results in different applications. For a person or group who views it as haram, this contract is not carried out. They prefer pawn. For groups that allow it, they apply the bai' al-wafa contract by referring to the opinions that allow it. The application of bai' al-wafa  depends on which reference is used as a basis. The research uses a qualitative approach with an analytical descriptive method based on field studies. The research locus is BMT Sidogiri. Data sources are taken from BMT managers. Data collection is done by interview, observation, and documentation. The data were analyzed in accordance with the characteristics of qualitative research. This research produced several findings. First, the mechanism of bai' al-wafa is in accordance with the opinion of the Hanafi school of thought which views that this contract includes 'urf. Second, in the analysis of muamalah fiqh, the bai' al-wafa contract at BMT Sidogiri is allowed because it contains the requirements of a valid contract and contains a side of benefit. The provisions for the permissibility of bai' al-wafa>' are regulated in the Compilation of Sharia Economic Law articles 112 to 115 Third, to avoid the assumption of ribawi, BMT applies multiple contracts, namely bai al-wafa with ijarah.